The Effect of Teaching Style Pratice, Reciprocity, Inclusion and Learning Motivation on Butterfly Swimming Skills - Rusdi Rusdi; Firmansyah Dlis; Johansyah Lubis; Anggri Dwi Nata; Whalsen Whalsen (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
Teaching styles have a very big role in improving students' learning abilities, by various learning styles it is hoped that students can find most appropriate teaching style that can improve student skills in learning, especially in the basic motion course of swimming. The training teaching style, reciprocity, inclusion of Mosston was selected in this study and learning motivation as the moderator variable was divided into 2 parts, they’re high and low. to determine the effect of teaching Style Pratice, reciprocal inclusion and learning motivation on butterfly swimming skills in male students at the Sports and Health Sciences Faculty. Method used in this study is an experimental method with a 3x2 factorial design. Subjects in the study were male students at the Sports and Health Education Faculty, Teachers' Training Institute, Indonesia Teachers Association, Pontianak. Based on the study results, it’s known that the reciprocal teaching style is better than teaching Style Pratice, the inclusion teaching style is better than the teaching Style Pratice and the inclusive teaching style, reciprocity is equally good in learning butterfly style swimming skills in male students at FPOK IKIP PGRI Pontianak.